Job Preferences of Aged Care Workers in Australia: Results from a Discrete Choice Experiment - Kostas Mavromaras; Linda Isherwood; Stephane Mahuteau; Julie Ratcliffe; Lily Xiao; Ann Harrington; Zhang Wei (Institute of Labor Economics (IZA), 2022)
Using a Discrete Choice Experiment we estimate the relative value attached by workers on core job attributes identified by previous qualitative research on the Aged Care workforce in Australia: salary (hourly); work hours; training/skill development; staffing numbers; processes for managing work-related stress; and freedom in the job. In this mostly part- time employed workforce, the opportunity for more workhours is welcome, but relatively less important. Nurses (enrolled and more so registered, being typically better-paid and higher-qualified) value pay rises less and training opportunities more than their (typically lower-paid and lower-qualified) care worker counterparts. Casual/temporary workers prefer workplaces that are adequately staffed relatively more than their permanently employed counterparts. In the context of increasing demand for more and for better-quality Aged Care services, the paper's overall findings can inform the current multi-faceted debate about a sustainable way for the Aged Care sector to attract, retain and utilize its workforce.
Keywords: J14; J21; J39; C25; I19; 330; aged care workforce; discrete choice experiments; job attributes; job preferences